NAVIGATING RADICAL DISRUPTION: A DYNAMIC CAPABILITIES PERSPECTIVE ON ORGANIZATIONAL RESILIENCE AND DIGITAL PIVOT IN HIGH-VELOCITY MARKETS - Kharis Adiputra; Umar Winarno; Suprayitno Suprayitno; Daniel Setiawan; Kaito Tanaka (Journal of Social Entrepreneurship and Creative Technology, 2026)
High-velocity markets are increasingly characterized by radical disruptions that challenge traditional organizational strategies and operational frameworks. Firms face continuous technological shocks, volatile customer demands, and competitive uncertainty, necessitating mechanisms that enable both rapid adaptation and sustained resilience. Understanding how organizations navigate these conditions is critical for maintaining competitiveness and long-term viability. The study aims to examine the interplay between dynamic capabilities and organizational resilience, focusing on the mediating role of digital pivot execution in high-velocity contexts. It seeks to elucidate the mechanisms through which sensing, seizing, and transforming capabilities are operationalized to enhance adaptive performance and strategic flexibility. A mixed-method research design was employed, integrating quantitative surveys from 112 organizations across technology, financial services, and e-commerce sectors with qualitative case studies and semi-structured interviews. Statistical analyses, including regression and structural equation modeling, were complemented by thematic coding of interview data to ensure contextual depth and triangulation. Results indicate that dynamic capabilities significantly enhance organizational resilience, with digital pivots functioning as a critical mediator. Sectoral differences reveal that technology firms leverage capabilities more effectively, whereas other industries require deliberate alignment strategies. Findings suggest that capability integration and strategic digital initiatives collectively drive adaptive performance. The study concludes that resilience is emergent from coordinated capability deployment and digital execution. Firms adopting integrated approaches demonstrate higher agility, operational continuity, and responsiveness to radical disruptions.